Nuclear DNA Fragmentation in Boar Spermatozoa: Measurement Methods and Reproductive Performance Implications - Ausejo, Raquel; Martínez, Juan Manuel; Mendoza, Noelia; Bolarin, Alfonso; Tejedor, M. Teresa; Falceto, Maria Victoria (Frontiers in Veterinary Science, 2022)
The aim of this research was to compare the different techniques to measure sperm nuclear DNA fragmentation (sDF) and check its relations to boar reproductive value, classical spermiogram parameters and reproductive results of the doses in sows. Sperm Chromatin Stability Assay (SCSA), Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and Sperm Chromatin Dispersion test (SCD, Halomax®) results were compared, finding a statistically significant correlation only between SCSA and TUNEL results. The fertility direct boar effect (DBE) index, calculated from the whole productive life of the boar, was not correlated (p>0.05) with sDF (measured by any technique). Total or progressive sperm motility was not correlated with sDF while it was found a positive correlation between TUNEL measure and abnormal acrosomes (%) and between SCD measure and total sperm morphological abnormalities (%). No significant correlations were obtained between fertility or prolificacy results and sDF results with the different techniques. However, in the case of total born and SCSA measure the correlation was close to significance (r partial = -0.095; p=0.066), appointing to a tendency; as SCSA increases the number of total piglets born decreases. In conclusion, although the different techniques for the sDF seem not to target exactly the same DNA events and the relationship between their values and the reproductive results and the classical spermiogram results is still to be elucidated, the studied sDF techniques may offer extra information that could be useful for the management of AI studs.